Pengembangan Lembar Kerja Elektronik Guided Inquiry Berbasis Website Materi Konsep Usaha dan Energi untuk Meningkatkan Keterampilan Proses Sains Peserta Didik dan Literasi Digital - Priskila Desmawati Lifire; Dadan Rosana (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2023)
This study aims to produce electronic worksheets that are: (1) feasible to use to improve science process skills and digital literacy in high school students; (2) practical to use to improve science process skills and digital literacy in high school students; and (3) assess the level of effectiveness in improving science process skills and digital literacy of high school students. This type of research is Research and Development using the ADDIE model, namely Analysis, Design, Develop, Implementation, and Evaluation. The field trial subjects consisted of 90 students of class X SMAN 2 Bangutapan which were divided into one experimental class and two comparison classes, the sample selection using a simple random sampling technique. The experimental class implemented electronic worksheets guided inquiry model and two comparison classes using conventional and contextual learning. The data collection instruments used were observation sheets, questionnaire sheets, and test questions. Data analysis techniques used feasibility analysis techniques based on the Aiken V value coefficient, practicality analysis based on the results of teacher and student response questionnaires, and effectiveness analysis based on observations of learning implementation and effect size. The results of the study stated that: (a) The website-based guided inquiry model electronic worksheet is declared feasible based on the results of the analysis of the validity of media feasibility and test questions; (b) The website-based guided inquiry model electronic worksheet is practical to use based on the results of the analysis of teacher and student responses; and (c) The website-based guided inquiry model electronic worksheet used in the learning process in improving students' science process skills and digital literacy with the results of the analysis based on the effect size measurement of the difference in the average scores of the three classes and the results of the analysis based on the effect size measurement in the medium category with effective criteria.